Antitumor effects of eribulin depend on modulation of the tumor microenvironment by vascular remodeling in mouse models. Issue 11 (22nd September 2017) - Ito, Ken; Hamamichi, Shusei; Abe, Takanori; Akagi, Tsuyoshi; Shirota, Hiroshi; Kawano, Satoshi; Asano, Makoto; Asano, Osamu; Yokoi, Akira; Matsui, Junji; Umeda, Izumi O.; Fujii, Hirofumi
Abstract : We previously reported that eribulin mesylate (eribulin), a tubulin‐binding drug (TBD), could remodel tumor vasculature (i.e. increase tumor vessels and perfusion) in human breast cancer xenograft models. However, the role of this vascular remodeling in antitumor effects is not fully understood. Here, we investigated the effects of eribulin‐induced vascular remodeling on antitumor activities in multiple human cancer xenograft models. Microvessel densities (MVD) were evaluated by immunohistochemistry (CD31 staining), and antitumor effects were examined in 10 human cancer xenograft models. Eribulin significantly increased MVD compared to the controls in six out of 10 models with a correlation between enhanced MVD levels and antitumor effects ( R 2  = 0.54). Because of increased MVD, we next used radiolabeled liposomes to examine whether eribulin treatment would result in increased tumoral accumulation levels of these macromolecules and, indeed, we found that eribulin, unlike vinorelbine (another TBD) enhanced them. As eribulin increased accumulation of radiolabeled liposomes, we postulated that this treatment might enhance the antitumor effect of Doxil (a liposomal anticancer agent) and facilitate recruitment of immune cells into the tumor. As expected, eribulin enhanced antitumor activity of Doxil in a post‐erlotinib treatment H1650 (PE‐H1650) xenograft model. Furthermore, infiltrating CD11b‐positive immune cells were significantly increased in multiple eribulin‐treated xenografted tumors, and natural killer (NK) cell depletion reduced the antitumor effects of eribulin. These findings suggest a contribution of the immune cells for antitumor activities of eribulin. Taken together, our results suggest that vascular remodeling induced by eribulin acts as a microenvironment modulator and, consequently, this alteration enhanced the antitumor effects of eribulin. Abstract : Eribulin, a nontaxane synthetic microtubule dynamic inhibitor, was approved by FDA and used for cancer treatment. Previously, we reported that eribulin induced vascular remodeling in the tumors by using preclinical mouse and rat xenograft models through increasing microvessel density, which consequently enhanced perfusion in the tumors (Funahashi et al., Cancer Sci., 105, 2014, 1334). Despite these advances, during eribulin treatment, a role of vascular remodeling for anti‐tumor effects is not fully elucidated. In this report, we further expanded our research by investigating pharmacological action of eribulin during the cancer treatment and found eribulin might function as a tumor microenvironment modulator in addition to its classic cytotoxic effect through vascular remodeling and contribute to effective cancer treatment.